Air‐stable Organobismuth(V) Bisperfluorooctanesulfonate as an Efficient Catalyst for the Synthesis of N‐Containing Compounds. Issue 8 (16th March 2016) - Wang, Penghui; Wang, Jinying; Au, Chak‐Tong; Qiu, Renhua; Xu, Xinhua; Yin, Shuang‐Feng
Abstract: Triphenyl bismuth bisperfluorooctanesulfonate is an air‐ and water‐stable Lewis acid. It exhibits high catalytic efficiency for the synthesis of nitrogen heterocycles such as diindolylmethane derivatives, dihydropyrimidinones, dihydropyridines and 1, 2‐disubstitued benzimidazoles under mild condition. Furthermore, it can be reused without loss of activity in a test of five cycles.This catalytic system affords a simple and efficient way for the synthesis of N‐containing compounds. Abstract :